On Marginal Automorphisms of Free Nilpotent Lie Algebras. (10th April 2020) - Öztekin, Özge
Abstract : Let L be the free nilpotent Lie algebra of finite rank over a field of characteristic zero. We define the concepts of marginal ideals and marginal automorphisms of L, and we give some results on marginal automorphisms.